Immature personality as basis for annulment in the light of Roman Rota judgments and ecclesiastical tribunals decisions - GOŁĘBIOWSKA, ANNA (Prawo Kanoniczne, 2012)
In manydecisionsof the Roman Rotaandjudgments of ecclesiastical tribunals, marriage was annulled because ofthe presence of immature personalityin thelitigantsthat makespeopleunableto take theessential obligations of marriage. From the analysis ofcourt records of the annulment ofmarriage result that inregards to marriage we can notspeakoffull maturity or the full maturityof marriage.We can speakonlyof a suitablematurity meaning the minimum and therefore the canonicalmaturity which is requiredby lawfora validmarriage.The studyof the canonicalprocessesfor annulmentof marriageshows that a person with animmaturepersonalityis not able tofulfillthe obligations arisingfrom the contract ofmarriage.In addition,processes analysisshowed that thenegativesymptoms ofan immature personalityinthe marriage usuallyexistedfrom the very beginningand that is whythe couplewere notable to establishdeeperemotional connections.